Estudo fitoquímico de Pavonia glazioviana Gurke e Sida rhombifolia L. (Malvaceae), preparação de derivados de criptolepinona, avaliação antimicrobiana e antioxidante dos compostos obtidos - Oliveira, Micaelly da Silva (2019)
Pavonia glazioviana Gurke (Malvaceae) is popularly known as "malva-dachapada" and et endemic Brazilian Caatinga and the species Sida rhombifolia L. (Malvaceae), popularly known as "matapasto" and "relógio", is native to world tropical areas and subtropical regions. The phytochemical study of P. glazioviana was carried out through usual chromatographic techniques, leading to the isolation of 12 compounds, identified through the data of the uni and bidimensional Nuclear Magnetic Resonance (1H NMR and 13C) spectra in addition to high resolution mass spectrometry. The ethanolic extract of P. glazioviana was evaluated for phenolic and total flavonoid content by spectrophotometric methods and antioxidant activity by the DPPH method. The study with the total alkaloid fraction (FAT) of S. rhombifolia was performed through UPLC-qTOF-MS/MS. From the FAT, derivatives of the cryptolepinone alkaloid were obtained by means of semisynthesis through alkylation semisynthesis, using potassium hydroxide, iodomethane and bromoethane. The isolated compounds of P. glazioviana and the derivatives obtained from cryptolepinone were evaluated for their antimicrobiological potential in vitro, using the microdilution technique. The isolates compounds were: 132-S-hydroxy-pheophytin a (Pg-1a), 132-S-hydroxy-173ethoxy-phophoride a (Pg-1b), 1-triacontanol (Pg-2), cis-p-coumaric acid ester (Pg-3), cicloart-23Z-ene-3β,25-diol (Pg-4), cycloart-25-ene-3β,24-diol (Pg-5), sitosterol-3-O-βD-glucopyranoside (Pg-6a), stigmasterol-3-O-β-D-glucopyranoside (Pg-6b), 5,7dihydroxy-3,8,4'-trimethoxyflavone (Pg-7) 5,7-dihydroxy-3,7,8,4’-tetramethoxyflavone (Pg-8), 5,7,4'-trihydroxy-3,8-dimethoxyflavone (Pg-9), 5,7,4'-trihydroxy-3methoxyflavone (Pg-10). The amount of phenol found in P. glazioviana was 48.40 mg of equivalents of gallic acid (EAG)/g of extract and of flavonoids was 33.68 ± 0.76 mg of quercetin equivalents (EQ)/g of extract and for antioxidant activity is CE50=6,36 mg/mL ± 0,03. The species P. glazioviana proved to be a good producer of phenolics and flavonoids, in addition to antioxidant potential. The FAT study allowed the identification of seven substances, namely: cryptolepine carboxylic acid (1), cryptolepin (2), quindoline (3), methoxyquinoline (4), quindolinone (5), cryptolepinone (6) and quindoline acid carboxylic methyl ester (7). Among the substances isolated from P. glazioviana, 5,7-dihydroxy-3,8,4'-trimethoxyflavone showed good antimicrobial activity and bacteriostatic/bactericidal and fungistatic/fungicidal potential against the strains tested, while substance cycloart-23Z-en-3β,25-diol showed moderate activity against the same microorganisms. It was possible to obtain two derivatives of cryptolepinone: 10-methylcryptolepinone (Dc-1) and 10-ethycryptolepinone (Dc-2), which presented anticrobial activity. 10-methylcryptolepinone was shown to be active at lower concentrations